Evaluation of executive and cognitive functions in bipolar patients and their family members - Behrooz Afshari; Zahra Zanjani (Fiyz̤, 2019)
Background: Bipolar disorder is a debilitating psychiatric disorder characterized by recurrent depression, manic, and hypomanic episodes. Examination and comparison of executive and cognitive functions in bipolar patients and their family members has not been addressed in Iran so far. The aim of the present study was to examine executive and cognitive functions in bipolar patients and their family members. Materials and Methods: In this cross-sectional study, 50 patients with bipolar disorder, 50 of their family members, and 50 healthy controls were included. The Young Mania Rating Scale, Beck Depression Inventory, Tower of London task, Wisconsin Card Sorting Task, Trail Making Test, Ruler Drop method, Four- Choice task, and general intelligence test were used to examine executive and cognitive functions of the participants. Results: Executive and cognitive functions in patients with a bipolar disorder were significantly lower than those in the other groups (P<0.01), but there was no significant difference in executive and cognitive functions between family members of the patients and healthy controls. Conclusion: According to the results of the present study, executive and cognitive functions have been destroyed in patients with bipolar disorder, but their family members have normal executive and cognitive functions.